Pelestarian Budaya Lokal untuk Menjaga Keutuhan Bangsa: Studi Hadis Riwayat Imam Ahmad No. 3418 - Nyimas Shoffah Shofiyatus Salamah (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the preservation of local culture as a form of effort to maintain the integrity of the nation. This study uses a qualitative approach by applying a descriptive-analytical method. The formal object of this research is hadith scholarship, while the material object is the hadith narrated by Imam Ahmad No. 3418 regarding maintenance of culture. The discussion of this research includes cultural development, cultural relations with Islam, and preservation of local culture ('urf) as an effort to maintain the integrity of the nation from a hadith perspective. The results of the discussion show that Rasulullah SAW. teaches the maintenance of 'urf (local culture) based on the hadith narrated by Imam Ahmad No. 3418, where 'urf is understood as a good habit that does not conflict with the essence of Islam. This study concludes that Islamic teachings regarding the preservation of local culture ('urf) play a major role as the basis for Muslims in efforts to protect the nation and state as a whole. This research is expected to have beneficial implications for enriching the treasures of Islamic knowledge, in particular it is hoped that it can become the basis for preserving local homeland culture in an effort to maintain the integrity of the Indonesian nation.